Productivity at Work: Impact of Personality Value and Organizational Commitment - Anco, Anco; Paudi, Untung La (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
The goal of this study was to clarify how organizational commitment and personality value characteristics affected labor productivity in groups of fisherman. In this study, 30 persons made up the sample, and questionnaires and interviews were employed to collect data. Multiple linear regression is the data analysis technique used with the SPSS 24 software. The findings of this study suggest that organizational commitment and personality values have a favorable and significant impact on work productivity. indicating a relationship in the same direction as the hypothesis, or that organizational commitment and personality values will boost job productivity in groups of fisherman.Keywords: Personality Value, Organizational Commitment, Work Productivity